Cos2x is just one of the crucial trigonometric identities offered in trigonometry to uncover the worth of the cosine trigonometric function for dual angles. That is also called a twin angle identity of the cosine function. The identity of cos2x helps in representing the cosine of a compound angle 2x in terms of sine and cosine trigonometric functions, in terms of cosine role only, in regards to sine duty only, and also in regards to tangent function only.

You are watching: Cos^2(x) =

Cos2x identity deserve to be derived using different trigonometric identities. Let us know the cos2x formula in terms of various trigonometric functions and its derivation in detail in the complying with sections. Also, us will discover the concept of cos^2x (cos square x) and its formula in this article.

 1 What is Cos2x? 2 What is Cos2x Formula in Trigonometry? 3 Derivation that Cos2x using Angle addition Formula 4 Cos2x In regards to sin x 5 Cos2x In regards to cos x 6 Cos2x In terms of tan x 7 Cos^2x (Cos Square x) 8 Cos^2x Formula 9 How to use Cos2x Identity? 10 FAQs ~ above Cos2x

Cos2x is critical trigonometric duty that is used to uncover the value of the cosine function for the link angle 2x. We deserve to express cos2x in state of different trigonometric functions and also each the its recipe is supplied to simplify facility trigonometric expressions and solve integration problems. Cos2x is a double angle trigonometric duty that determines the worth of cos once the angle x is doubled.

Cos2x is vital identity in trigonometry which deserve to be express in various ways. It deserve to be express in state of various trigonometric features such together sine, cosine, and tangent. Cos2x is among the double angle trigonometric identities as the edge in factor to consider is a many of 2, the is, the dual of x. Let united state write the cos2x identification in various forms:

cos2x = cos2x - sin2xcos2x = 2cos2x - 1cos2x = 1 - 2sin2xcos2x = (1 - tan2x)/(1 + tan2x) We understand that the cos2x formula deserve to be expressed in four various forms. We will usage the angle addition formula because that the cosine function to derive the cos2x identity. Note that the angle 2x have the right to be written as 2x = x + x. Also, we recognize that cos (a + b) = cos a cos b - sin a sin b. Us will usage this to prove the identity for cos2x. Utilizing the angle addition formula for cosine function, substitute a = b = x into the formula because that cos (a + b).

cos2x = cos (x + x)

= cos x cos x - sin x sin x

= cos2x - sin2x

Hence, we have actually cos2x = cos2x - sin2x

Now, that we have acquired cos2x = cos2x - sin2x, we will derive the formula because that cos2x in terms of sine function only. We will usage the trigonometry identification cos2x + sin2x = 1 to prove the cos2x = 1 - 2sin2x. Us have,

cos2x = cos2x - sin2x

= (1 - sin2x) - sin2x

= 1 - sin2x - sin2x

= 1 - 2sin2x

Hence, we have actually cos2x = 1 - 2sin2x in terms of sin x.

Just choose we acquired cos2x = 1 - 2sin2x, we will certainly derive cos2x in regards to cos x, the is, cos2x = 2cos2x - 1. We will use the trigonometry identities cos2x = cos2x - sin2x and also cos2x + sin2x = 1 come prove the cos2x = 2cos2x - 1. Us have,

cos2x = cos2x - sin2x

= cos2x - (1 - cos2x)

= cos2x - 1 + cos2x

= 2cos2x - 1

Hence , we have cos2x = 2cos2x - 1 in regards to cosx

Now, that us have obtained cos2x = cos2x - sin2x, we will certainly derive cos2x in terms of tan x. We will use a few trigonometric identities and also trigonometric recipe such as cos2x = cos2x - sin2x, cos2x + sin2x = 1, and also tan x = sin x/ cos x. Us have,

cos2x = cos2x - sin2x

= (cos2x - sin2x)/1

= (cos2x - sin2x)/( cos2x + sin2x)

Divide the numerator and denominator that (cos2x - sin2x)/( cos2x + sin2x) by cos2x.

(cos2x - sin2x)/(cos2x + sin2x) = (cos2x/cos2x - sin2x/cos2x)/( cos2x/cos2x + sin2x/cos2x)

= (1 - tan2x)/(1 + tan2x)

Hence, we have cos2x = (1 - tan2x)/(1 + tan2x) in regards to tan x

Cos^2x is a trigonometric function that implies cos x whole squared. Cos square x deserve to be to express in various forms in terms of different trigonometric features such together cosine function, and also the sine function. We will use different trigonometric formulas and also identities to derive the recipe of cos^2x. In the following section, let united state go v the recipe of cos^2x and their proofs.

To come at the recipe of cos^2x, we will certainly use assorted trigonometric formulas. The very first formula that we will use is sin^2x + cos^2x = 1 (Pythagorean identity). Utilizing this formula, subtract sin^2x indigenous both political parties of the equation, we have sin^2x + cos^2x -sin^2x = 1 -sin^2x which suggests cos^2x = 1 - sin^2x. 2 trigonometric recipe that has cos^2x are cos2x formulas provided by cos2x = cos^2x - sin^2x and cos2x = 2cos^2x - 1. Making use of these formulas, we have actually cos^2x = cos2x + sin^2x and cos^2x = (cos2x + 1)/2. Therefore, the formulas of cos^2x are:

cos^2x = 1 - sin^2x ⇒ cos2x = 1 - sin2xcos^2x = cos2x + sin^2x ⇒ cos2x = cos2x + sin2xcos^2x = (cos2x + 1)/2 ⇒ cos2x = (cos2x + 1)/2

Cos2x formula can be offered for solving different math problems. Let united state consider an instance to recognize the application of cos2x formula. Us will determine the worth of cos 120° using the cos2x identity. We understand that cos2x = cos2x - sin2x and also sin 60° = √3/2, cos 60° = 1/2. Because 2x = 120°, x = 60°. Therefore, us have

cos 120° = cos260° - sin260°

= (1/2)2 - (√3/2)2

= 1/4 - 3/4

= -1/2

Important note on Cos 2x

cos2x = cos2x - sin2xcos2x = 2cos2x - 1cos2x = 1 - 2sin2xcos2x = (1 - tan2x)/(1 + tan2x)The formula for cos^2x that is generally used in integration troubles is cos^2x = (cos2x + 1)/2.The derivative of cos2x is -2 sin 2x and the integral the cos2x is (1/2) sin 2x + C.

☛ connected Topics:

Example 2: refer the cos2x formula in terms of cot x.

See more: How Do Hen And Rooster Mate : The Complete Guide, All You Need To Know

Solution: We understand that cos2x = (1 - tan2x)/(1 + tan2x) and tan x = 1/cot x

cos2x = (1 - tan2x)/(1 + tan2x)

= (1 - 1/cot2x)/(1 + 1/cot2x)

= (cot2x - 1)/(cot2x + 1)

Answer: Hence, cos2x = (cot2x - 1)/(cot2x + 1) in terms of cotangent function.